miR-126 contributes to the epigenetic signature of diabetic vascular smooth muscle and enhances antirestenosis effects of Kv1.3 blockers - Marycarmen Arevalo-Martinez; Pilar Cidad; Sara Moreno-Estar; Mirella Fernández; Sebastian Albinsson; Irene Cózar-Castellano; José R. López-López; M. Teresa Pérez-Garcia (Elsevier, 2021)
Objectives: Restenosis after vessel angioplasty due to dedifferentiation of the vascular smooth muscle cells (VSMCs) limits the success of surgical treatment of vascular occlusions. Type 2 diabetes (T2DM) has a major impact on restenosis, with patients exhibiting more aggressive forms of vascular disease and poorer outcomes after surgery. Kv1.3 channels are critical players in VSMC proliferation. Kv1.3 blockers inhibit VSMCs MEK/ERK signalling and prevent vessel restenosis. We hypothesize that dysregulation of microRNAs (miR) play critical roles in adverse remodelling, contributing to Kv1.3 blockers efficacy in T2DM VSMCs. Methods and results: We used clinically relevant in vivo models of vascular risk factors (VRF) and vessels and VSMCs from T2DM patients. Resukts: Human T2DM vessels showed increased remodelling, and changes persisted in culture, with augmented VSMCs migration and proliferation. Moreover, there were downregulation of PI3K/AKT/mTOR and upregulation of MEK/ERK pathways, with increased miR-126 expression. The inhibitory effects of Kv1.3 blockers on remodelling were significantly enhanced in T2DM VSMCs and in VRF model. Finally, miR-126 overexpression confered "diabetic" phenotype to non-T2DM VSMCs by downregulating PI3K/AKT axis. Conclusions: miR-126 plays crucial roles in T2DM VSMC metabolic memory through activation of MEK/ERK pathway, enhancing the efficacy of Kv1.3 blockers in the prevention of restenosis in T2DM patients.